The impact of supplier dependence on suppliers' CSR: The moderating role of industrial dynamism and corporate transparency. Issue 5 (December 2021) - Zhang, Zhe; Hu, Dan; Liang, Liang
Abstract: To improve corporate social responsibility (CSR) in the supply chain, focal buyers may use supplier dependence to influence the supplier's resource strategy to promote the supplier's CSR initiatives. Thus, supplier dependence is particularly critical to the supplier's CSR, especially for Chinese suppliers with resource constraints. However, there is limited understanding and research on the degree to which a supplier depends on major buyers for the supplier's CSR from the supplier's perspective. Based on a sample of 284 Chinese listed companies, this study analyses the relationship between supplier dependence and suppliers' CSR through the lens of resource dependence theory (RDT). In addition, we investigate the moderating roles of industrial dynamism and corporate transparency in the relationship between supplier dependence and suppliers' CSR. The results indicate that supplier dependence has a negative impact on the Chinese supplier's CSR performance. Meanwhile, the negative impact of supplier dependence is mitigated for the supplier's more volatile industrial context, while improving corporate transparency enhances the negative impact of supplier dependence. This study verifies the applicability of RDT for the analysis of CSR in the supply chain in emerging markets such as China. Moreover, the study further extends research on the role of buyer-supplier relationships in CSR in the supply chain by extending the research perspective to the supplier side and adding the external and internal uncertainty of the supplier to the theoretical framework for analysis. We also provide managerial implications for implementing Chinese suppliers' CSR from the buyer's and supplier's perspectives. Highlights: This study highlights the critical role of supplier dependence on suppliers' CSR. Supplier dependence negatively impacts the Chinese supplier's CSR performance. Industrial dynamism mitigates the negative effect of supplier dependence on Chinese suppliers' CSR performance. Corporate transparency aggravates the negative effect of supplier dependence on Chinese suppliers' CSR performance. We provide key implications for CSR in the supply chain.